Implementasi Program Kartu Indonesia Pintar di Kota Batam - Putra Anggiat Marito Pasaribu; Nazaki Nazaki; Novi Winarti (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
The Smart Indonesia Card Early Program ran precisely in 2016, there was a procedural error in obtaining the program, so many people were disappointed with this because the beneficiary program was not precise in obtaining KIP. The purpose of this research is to find out the implementation of procedures related to the Indonesia Smart Card Program in Batam City. In this study, the researcher used a descriptive research type using a qualitative approach with 7 informants and used techniques and data collection in the form of interviews and documentation, while the object of this research was the Indonesia Smart Card Program. The location of this research was conducted in Batam City, the actors involved in this research were the KIP Program Recipient Communities, School Parties from elementary, junior high, high school and the Batam City Education Office. Coordinating performance is the right thing in every policy implementation, it is very effective because it starts from the initial stage to maximum results. Giving assignments will make it easier to carry out, support from the leadership is the basic form in building the mentality of the implementer so that they can be confident in carrying out the program to be carried out. Based on the results of research and analysis conducted by researchers regarding the implementation of the smart Indonesian card program in Batam City, it can be concluded that the implementation of the program is correct in the procedure for obtaining the Indonesian smart card program. Everything is structured in the division of tasks and responsibilities, so as to provide results who is good in data collection, inputting to the final stage in determining the right or wrong beneficiary program.